Conceptualization of e-Learning Theories and Approaches in the context of Further and Higher Education - Hegde Lata Narayan; Shailashri V. T, (International Journal of Applied Engineering and Management Letters (IJAEML), 2020)
E-Learning is an innovative system of learning technology. It’s a multidisciplinary process. Because of fast growth of internet technology, educational institutions and universities worldwide are diverting their investment in e-learning technology to support their traditional methods of teaching. It develops learner’s experience, knowledge and the action of performing a task or function efficiently. The success of e-Learning depends on two ingredients 1. Technological factor (software and hardware is used to build e-Learning systems).2. Human factor (Students and Faculty). These e-Learning systems are divided into three interfaces, Student, faculty and institution. E-Learning is technology based educational tool for learning. e-Learning is becoming more prominent in the world of higher and further education. eLearning is a powerful tool that can help and transform education in many ways. e-Learning is imparting of education through digital media, personal computers, DVDs, mobile phones and the Internet. Through the use of modern technological resources, e-Learning programs make it possible for many students to achieve their educational goals. Most of the countries adopt traditional classroom teaching practice for imparting knowledge, which is fast vanishing. The latest classroom adopts a more interactive environment using e-learning content such as applications of new e-learning software, internet-driven instructors to disseminate more personalized learning experiences to individual student working with laptops, tablets, android mobiles and other electronic learning devices. In this scenario, e-Learning is network enabled transfer of soft-skills and knowledge. E-learning includes computer-based learning, web-based learning, internet-driven software packages, virtual classrooms and digital applications. This study on e-learning is based on secondary data, focuses on history, types, forms, merits and demerits of e-learning to the students and faculty. It also deals with scope, difference between traditional & e-learning and challenges to students and instructors. The study uses swot analysis to conceptualize e-Learning.